The Effect of Promotion, Reference Group, Brand Reputation and Motivation on the Decision to Choose a High School of Administrative Science in Southern Kalimantan with Electronic Word of Mouth (E-Wom) as an Intervening Variable - Asmawatiy, Cici; Said, Laila Refiana; khariry, Mukhlan (East Asian Journal of Multidisciplinary Research, 2024)
With Electronic Word of Mouth (Z) acting as an intervening variable, this study attempts to examine the impacts of promotion (X1), reference group (X2), brand reputation (X3), and motivation (X4) on the decision to pick (Y) the College of Administrative Sciences in South Kalimantan. Students from private universities in South Kalimantan, such as STIA Bina Banua Banjarmasin, Amuntai, and Tabalong, participate in the study. The sample size is 477, and the population is made up of 5,536 enrolled students from 2017 to 2021. Through the use of Structural Equation Modeling (SEM) and Path Analysis via Smart-PLS, the study comes to the conclusion that e-WoM is greatly impacted by motivation, brand reputation, and promotion, while e-WoM and reference groups have an impact on decision-making.